Evaluation of testicular toxicity upon fetal exposure to bisphenol A using an organ culture method. (May 2021) - Park, Hyun-Jung; Lee, Won-Young; Do, Jeong Tae; Park, Chankyu; Song, Hyuk
Abstract: Humans are exposed to a multitude of endocrine disruptor chemicals (EDCs) that can interfere with the action of endogenous hormones and the normal development of reproductive organs. Bisphenol A (BPA) is one of the most common EDCs found in the environment. Here, we evaluated BPA toxicity on fetal testes using an in vitro organ culture system. Mouse fetal testes sampled at 15.5 days post coitus were cultured in a medium containing BPA for 5 days. The number of germ cells was reduced by BPA treatment, whereas the number of Sertoli cells was slightly increased by BPA at the highest dose (100 μM). Consistently, BPA treatment reduced the protein and gene expression levels of germ cell markers, but it increased the expression levels of Sertoli cell markers. The expression levels of fetal Leydig cell markers such as Cyp11a1, Thbs2, Cyp17a1, and Pdgf-α were significantly increased, whereas those of adult Leydig cell markers such as Hsd17b3, Ptgds, Sult1e1, Vcam1, and Hsd11b1 were decreased in the testes exposed to BPA. Generally, Notch signaling restricts Leydig cell differentiation from progenitor cells during fetal testis development. The expression levels of Notch1, Notch2, Notch3, Hes1, Ptch1, Jag1, Jag2, c-Myc, Hey1, and Hey2, which are involved in Notch signaling, were markedly higher in BPA-treated fetal testes than in the controls, indicating that BPA interrupts fetal Leydig cell development. BPA also disrupted steroidogenesis in the fetal testis organ culture system. In conclusion, our study showed that BPA inhibits fetal germ cell growth, Leydig cell development, and steroidogenesis. Graphical abstract: Image 1 Highlights: BPA toxicity in fetal testes was assessed in an in vitro organ culture system. Culture for 5 days in BPA reduced germ cells and slightly increased Sertoli cells. BPA downregulated the expression of germ cell markers. BPA upregulated the expression of Sertoli cell markers. BPA increased Notch signaling gene levels to suppress fetal Leydig cell development.